2010
DOI: 10.5137/1019-5149.jtn.3574-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of pulsatility index with intracranial pressure in traumatic brain injury

Abstract: AIm:In traumatic brain injury (TBI) patients, it is desired to monitor the intracranial pressure (ICP) to assess the cerebral haemodynamics and guide the therapy. The study was designed to see if the pulsatility index (PI) measured by transcranial Doppler ultrasonography (TCD) predicts information about ICP values. mAterIAl and methOds:In 52 TBI patients with Glasgow Coma Scale (GCS) score < 9, invasive intracranial monitoring and TCD ultrasonography for PI were performed through five days. ICP, cerebral perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…A PI > 1.4 correlates with an ICP > 15 mm Hg and a decreased CPP [10]. Although the formula 10.93 × PI) -1.28 has been suggested for ICP measurement, TCD remains more useful in the monitoring of ICP changes rather than providing an exact value [11,12]. Likewise, while TCD can screen for brain death, it is not definitive due to the inability to scan the posterior circulation.…”
Section: Probe Position and Measurementsmentioning
confidence: 99%
“…A PI > 1.4 correlates with an ICP > 15 mm Hg and a decreased CPP [10]. Although the formula 10.93 × PI) -1.28 has been suggested for ICP measurement, TCD remains more useful in the monitoring of ICP changes rather than providing an exact value [11,12]. Likewise, while TCD can screen for brain death, it is not definitive due to the inability to scan the posterior circulation.…”
Section: Probe Position and Measurementsmentioning
confidence: 99%
“…Similarly, assessing the intracranial vessels pulsation is made possible using transcranial doppler (TCD) and measuring the velocity of middle cerebral artery (MCA) and quoted as pulsatility (PI) or resistive index (RI). Researchers have found strong correlation between the RI or PI with raised ICP (Bellner et al, 2004;Gura et al, 2011;Voulgaris et al, 2005). Fig.…”
Section: Monro-kellie Doctrine Cerebral Autoregulation Cerebral Pulmentioning
confidence: 99%
“…They concluded that the PI may provide guidance in those patients with suspected intracranial hypertension and that repeated measurements may be of use in the neurocritical care unit. There is significant evidence that independent of the type of intracranial pathology, a strong correlation between PI and ICP exists [12,[18][19][20]. A recent study indicated that TCD had 94% of sensitivity to identify high ICP/low CPP at admission and a negative predictive value of 95% to identify normal ICP at admission; the sensitivity to predict abnormal cerebral perfusion pressure was 80% [20].…”
Section: Discussionmentioning
confidence: 95%